2016
DOI: 10.5032/jae.2016.01073
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Self-Efficacy Theory in Agricultural Education

Abstract: This research sought to evaluate the use of the self-efficacy theory in agricultural education. A total of 30 studies, published between 1997 and 2013 using self-efficacy as a theoretical foundation were compiled and analyzed. The findings of these studies were compared to expected outcomes identified by the self-efficacy theory, specifically the positive relationship between Bandura's four identified self-efficacy building experiences and increased self-efficacy as well as the relationship between self-effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 29 publications
0
32
0
Order By: Relevance
“…The unique aspect of the relationship between years of teaching experience and selfefficacy was it not being seen in the other self-efficacy areas (i.e., instructional strategies, math teaching, and science teaching). Based on the theoretical foundations of self-efficacy, we could confidently assume more years of teaching experience would yield additional opportunities to experience success in instructional strategies, teaching math, and teaching science (Bandura, 1986;McKim & Velez, 2016). One unique difference between the teaching areas found to relate to years of teaching experience (i.e., leading students and classroom management) and the teaching areas not found to relate (i.e., instructional strategies, math teaching, science teaching) is the emphasis on content.…”
Section: Years Of Teaching Experiencementioning
confidence: 99%
“…The unique aspect of the relationship between years of teaching experience and selfefficacy was it not being seen in the other self-efficacy areas (i.e., instructional strategies, math teaching, and science teaching). Based on the theoretical foundations of self-efficacy, we could confidently assume more years of teaching experience would yield additional opportunities to experience success in instructional strategies, teaching math, and teaching science (Bandura, 1986;McKim & Velez, 2016). One unique difference between the teaching areas found to relate to years of teaching experience (i.e., leading students and classroom management) and the teaching areas not found to relate (i.e., instructional strategies, math teaching, science teaching) is the emphasis on content.…”
Section: Years Of Teaching Experiencementioning
confidence: 99%
“…The positive relationship between social community and general self-efficacy supports the relationship between peer environment and student outcomes posited within the model of postsecondary student retention and success proposed by Terenzini and Reason (2005). In addition, the relationship between social dynamics and self-efficacy is supported by the theoretical foundations of self-efficacy, which suggest social persuasion (i.e., social reinforcement from respected others) as a building block of self-efficacy (Bandura, 1997;McKim & Velez, 2016). In combination, these findings reinforce the importance of building a positive social culture within AFNR education programs, which is explored further within the recommendations.…”
Section: Conclusion and Discussionmentioning
confidence: 66%
“…Teacher education programs play an important role in the development of beginning teacher self-efficacy. Tschannen-Moran and Hoy (2001) suggested that supporting the development of teacher self-efficacy is essential for producing effective, committed, and enthusiastic teachers, and should begin during teacher education coursework; a recommendation supported in AFNR education (McKim & Velez, 2016). Consequently, AFNR education programs that seek to produce effective, committed, and enthusiastic teachers in the AFNR pipeline, should strive to support the development of student self-efficacy.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature revealed there is minimal research in regard to mastery experiences and self-efficacy in high school agricultural education students. McKim and Velez (2016) found limited research relating to vicarious experiences and agricultural education. Social persuasion has been seen in the literature in regard to teacher preparation where "encouragement could come by way of formal and informal observations, affirmation of departmental tasks completed, or restating positive comments from students about the early career teacher" (McKim, Velez, & Clement, 2017, p. 294).…”
Section: Self-efficacymentioning
confidence: 99%